Adaptative responses of myenteric neurons of Sphoeroides testudineus to environmental pollution - Nascimento Goncalves, Alexandre Rodrigo [UNESP]; Marinsek, Gabriela Pustiglione [UNESP]; Souza Abessa, Denis Moledo de [UNESP]; Mari, Renata de Britto [UNESP] (Elsevier B.V., 2020)
Contamination in estuarine regions affects the local biota damaging the ecosystems and reaching humans. The gastrointestinal tract is a dynamic environment capable of obtaining nutrients and energy from food while it protects the host against harmful toxins and pathogens from the external environment. These functions are modulated by the enteric nervous system and changes in its structure can result in gastrointestinal disorders. The objective of this study was to evaluate if the environmental contaminants have effects on the myenteric neuronal plasticity of pufferfish Sphoeroides testudineus. Animals were collected in Barra do Una River, located at Jureia-Itatins Mosaic of Protected Areas (reference area - RA) and in the Santos Estuarine System (impacted area - IA). Morpho-quantitative analyses of the general and metabolically active myenteric neuronal populations of the proximal and distal intestine were made. Disarrangement was observed in the general organization of the myenteric plexus, with an expressive reduction of the neuronal groups (nodes) in the animals of IA. The vulnerability of the myenteric plexus was evidenced by a decrease in density and cellular profile of the general neuronal population, followed by an increase of the metabolism of the remaining neurons, which in turn was verified by a growth of the area of the cellular and nuclear profiles of the metabolically active neuronal population. Through these analyses, we concluded that animals inhabiting polluted regions present alterations in the myenteric neuronal plasticity, as a way of maintaining the functions of the gastrointestinal tract.
Keywords: Enteric nervous system; Pollution; Environmental quality assessment; Neuronal plasticity; Pufferfish